Training Preschoolers on First‐Order False Belief Understanding: Transfer on Advanced ToM Skills and Metamemory. Issue 6 (14th July 2014) - Lecce, Serena; Bianco, Federica; Demicheli, Patrizia; Cavallini, Elena
<x xml:space="preserve">Abstract</x> This study investigated the relation between theory of mind (ToM) and metamemory knowledge using a training methodology. Sixty‐two 4‐ to 5‐year‐old children were recruited and randomly assigned to one of two training conditions: A first‐order false belief (ToM) and a control condition. Intervention and control groups were equivalent at pretest for age, parents' education, verbal ability, inhibition, and ToM. Results showed that after the intervention children in the ToM group improved in their first‐order false belief understanding significantly more than children in the control condition. Crucially, the positive effect of the ToM intervention was stable over 2 months and generalized to more complex ToM tasks and metamemory.